2001
DOI: 10.1177/153537020122601107
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Mediators in Gastrointestinal Defense and Injury

Abstract: Inflammation of the mucosal layer of the gastrointestinal (GI) tract Is not only a feature almost always associated with ulceration of those tissues, but it also plays an Important role In both the production and healing of the lesions. The mediators that coordinate inflammatory responses also have the capability to alter the resistance of the mucosa to Injury Induced by noxious substances, while others render the mucosa more susceptible to injury. In this article, we provide a review of the inflammatory media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
68
1
10

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(83 citation statements)
references
References 160 publications
4
68
1
10
Order By: Relevance
“…14 The central importance of prostaglandins in epithelial mucosal function has been demonstrated by the ulcerogenic effect of nonsteroidal antiinflammatory drugs (NSAIDS) in the gastrointestinal tract. [15][16][17] This is consistent with the protective effect of prostaglandins against ulcers in the gastrointestinal tract of both human and animal models. 18 -21 Elevated concentrations of prostaglandins in IBD were first described by Gould et al, 22 and confirmed by others.…”
Section: Discussionsupporting
confidence: 69%
“…14 The central importance of prostaglandins in epithelial mucosal function has been demonstrated by the ulcerogenic effect of nonsteroidal antiinflammatory drugs (NSAIDS) in the gastrointestinal tract. [15][16][17] This is consistent with the protective effect of prostaglandins against ulcers in the gastrointestinal tract of both human and animal models. 18 -21 Elevated concentrations of prostaglandins in IBD were first described by Gould et al, 22 and confirmed by others.…”
Section: Discussionsupporting
confidence: 69%
“…Conceivably, the increase in oxidative stress in the aforementioned groups was shown, in the current study, by SOD concentration. It has also been demonstrated that LTB4 intracolonic administration provokes increased tissue damage in rats with colitis and that LTB4 antagonist utilization as well as 5-LPO inhibitors can attenuate leukocytes adhesion and reduce colonic damage severity induced by NSAIDs (54) . In the present experiment, there were no significant differences in LTB4 concentration when the control group was compared to the colitis group, similarly to the results obtained by Nieto et al (41) in experimental colitis induced by TNBS.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is reported that those cytokines are produced from inflammatory sites, functioning as inflammatory mediators in the process of gastric ulcer healing. 13,26,27,28 Taken together, it is reasonable to speculate that these inflammatory cytokines were secreted from the site of the injury and delivered to the cells located around the ulcerated craters, resulting in the activation of the Tg promoter (hCMV promoter). We confirmed that these cytokine genes are indeed upregulated in Tg stomachs in response to HCl/ethanol administration ( Figure 5c).…”
Section: Discussionmentioning
confidence: 99%